EFFECT OF DIETARY ZEOLITE ON AMMONIA TOXICITY AND ON SOME OF BLOOD PARAMETERS IN COMMON CARP CYPRINUS CARPIO - Abdulathem, Alaa A.; Al-Rudainy, Abdulmotalib J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The present study aimed to evaluate the effect of dietary zeolite on ammonia toxicity and in some of blood parameters in Cyprinus carpio. Fish were fed either a control diets (0% zeolite) or control diet supplemented with 2, 4 and 6% (T1, T2 and T3) respectively for 28 days. Results showed that the mean value of ammonia concentrations ranged between 0.10 mg/l in T1 and T3 in the first week to 1.85 mg/l in control in fourth week, which could be noticed a gradually increased in the values of ammonia in the end of the experiment. Results showed that the ammonia concentration has a significant (p≤ 0.05) increased in control treatment for third and fourth week compared with other treatments. For blood parameters, results showed high fluctuation in the mean values of RBC count, the mean of WBC count recorded the highest value in control treatment, and significantly decreased in T1,T2 and T3. PCV value and Hb content recorded the lowest values in control treatment and the highest values in T1,T2 and T3 respectively. It can be concluded that T3 have reached the saturation point for lower values in the first three weeks of ammonia , then the active of zeolite decreased resulted increasing ammonia in fourth week for all treatments.